THE SAS METHOD TO IMPROVE EARLY READING SKILLS IN PRIMARY SCHOOL CHILDREN - Salsabila, Mutiara; Sugiharti, Rini Endah; Nurcholidah Anisa, Ririn (ATTA`DIB, 2025)
Language is the main component that determines progress in science, the ability of the younger generation to use language greatly affects the level of education of a country. Reading is a language skill that should be learnt at an early age. This skill is divided into beginner and advanced levels. In grades one and two. Reading skills are taught so that students recognise letters, syllables, words and sentences. Failure to start reading can impact on comprehension of other material. Studies show that the Structural Analytic Synthetic (SAS) method works effectively in improving the reading skills of beginning students. It has a systematic and planned procedure to analyse and combine letter symbols into words and sentences. Many researchers have shown that this method improves students. Therefore, this technique can be a solution to overcome students who have poor initial reading skills at the primary level. To find and analyse relevant literature regarding the application of the SAS method in beginning reading, the researcher used the study literature review (SLR) method for this research.